(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Speech-to-Text (STT) and Text-to-Speech (TTS) recognition technologies have witnessed significant advancements in recent years, transforming various industries and applications. STT allows for the conversion of spoken language into written text, while TTS enables the generation of natural-sounding speech from written text. In this research paper, we provide a comprehensive review of the latest advancements in STT and TTS recognition technologies, including their underlying methodologies, applications, challenges, and future directions. We begin by discussing the key components of STT and TTS systems, including automatic speech recognition (ASR) and speech synthesis techniques. We highlight the evolution of these technologies, from traditional approaches to data-driven deep learning methods, such as convolutional neural networks (CNNs), recurrent neural networks (RNNs), and transformerbased models. We then examine the various applications of STT and TTS recognition technologies in different domains, including healthcare, customer service, accessibility, and language translation. We discuss the benefits of STT and TTS in improving communication, accessibility, and user experience, and address the challenges and limitations of these technologies, such as accuracy in noisy environments, handling diverse accents and languages, context awareness, and ethical considerations. We highlight the ongoing research efforts to address these challenges and improve the performance and robustness of STT and TTS systems. Finally, we outline the future directions and potential research opportunities in STT and TTS, including advancements in deep learning techniques, multimodal integration, domain adaptation, and personalized speech synthesis. We emphasize the importance of interdisciplinary research collaborations, data collection, and benchmarking efforts to further drive the development and deployment of STT and TTS recognition technologies in real-world applications.